Analysis of Students' Self Efficacy in Science Learning (Unnes Science Education Journal, 2022)
Distrust of students’ abilities will have an impact on the process and expected results in learning. With self-efficacy in students, it will require students to behave steadily and effectively in learning. This study aims to identify students’ self-efficacy in learning science. Students are expected to have self-potential and develop a level of confidence in their ability to do or achieve learning goals. The survey research was conducted on 30 students of class IX SMPN in Padang City. Data was collected using a questionnaire based on self efficacy indicators with 15 questions. The results of the analysis of the data obtained that the self-efficacy level of class IX students of SMPN in Padang City is 70.94 with a high category. This means that both teachers and students have actively worked together in the success of the science learning process in the classroom.